Protocatechuic acid induces apoptosis in human osteosarcoma cells by regulating P13K/AKT/ROS pathway - Mei, Qiyuan; Chen, Xiaohu; Liu, Wei (Penerbit Universiti Kebangsaan Malaysia, 2022)
Previous investigations have demonstrated that protocatechuic acid (PCA) provides anti-tumour properties in different tumour cell types. It does, however, have an unknown cause on osteosarcoma cells. In this investigation, the underlying mechanism of the effect of PCA on osteosarcoma cells (MNNG or HOS) was investigated and established. The viability of the cell was assessed with the MTT test. Acridine orange/ethidium bromide staining and Western blot analysis were conducted for assessment of cell apoptosis. Western blot analysis was identified for cell cycle progression. In addition to establishing the above findings, the Western blot analysis demonstrated that PCA mediated osteosarcoma cellular apoptosis by triggering the apoptotic pathway of Caspase-9. Additionally, we found that PCA considerably stimulated osteosarcoma cell apoptosis and arrest of cell cycle proliferation by controlling a pathway involving P13K/Akt/ROS signalling. In short, we observed that PCA prevented the advancement of osteosarcoma through the stimulation of apoptosis in osteosarcoma cells. The mechanism underlying this study also showed that PCA generated effective anti-tumour activity on osteosarcoma cells by controlling the signalling pathways of P13K/Akt/ROS.